OP0095 INFLUENCE OF PERIODONTITIS ON DISEASE ACTIVITY, PHYSICAL FUNCTION, AND SAFETY IN PATIENTS WITH RHEUMATOID ARTHRITIS: A OBSERVATIONAL STUDY USING THE IORRA COHORT. (June 2019) - Hayashi, Mayuko; Sakai, Ryoko; Tanaka, Eiichi; Furuya, Takefumi; Inoue, Eisuke; Abe, Mai; Kawano, Mika; Sugano, Eri; Sugitani, Naohiro; Saka, Kumiko; Ochiai, Moeko; Shimizu, Yoko; et al.
Abstract : Background: Periodontitis (PD) is considered to be one of the triggers for rheumatoid arthritis (RA) 1 . Several reports demonstrated the associations between the disease activity of RA and presence of PD, however, most of them are based on small population, and results are inconsistent 2, 3 . Furthermore, impact of PD on physical function and safety is not known. Thus, a study using a large cohort database is warranted to clarify the relationship between patients' outcomes and PD among patients with RA. Objectives: To demonstrate the influence of PD on the outcome of RA, an established cohort IORRA database was used to compare the disease activity, physical function and prevalence of infection between patients with PD and those without. Methods: IORRA database is an established cohort database with RA in our institute since 2000. Trough biannual data collection including patient's questionnaire, physician's evaluations and laboratory data in more than 5, 000 RA patients, a database with a total 91, 884 patient-year observation period was established by 2018. In this IORRA database, RA patients who answered to all the questionnaires about PD in October 2016 were extracted. Among those, we defined patients with PD (PD group) as having diagnosis of PD during the last 6 months, and those without PD (non-PD group) as having no present and previous PD. Using the data set from April 2016 to October 2016, we compared Disease Activity Score 28 (DAS28), Japanese Health Assessment Questionnaire (J-HAQ) score, and the prevalence of patients self- reported infections required hospitalizations or hospital visits between the two groups. For background data comparisons, we used chi-squared test for categorical data and Mann-Whitney U-test for continuous data. To investigate associations between PD and remission or PD and infection, we calculated adjusted odds ratio (OR) of PD using a logistic regression model. Results: At baseline, patients in the PD group (n=925) were significantly older, had higher DAS28 and J-HAQ than those in the non-PD group (n=2, 583). DAS28 and J-HAQ at 6 month in the PD group were significantly higher than those of the non-PD group (DAS28, 2.60 in PD group, 2.42 in non-PD group, p<0.001; J-HAQ score, 0.25 in PD group, 0.13 in non-PD group, p<0.001). Median of delta DAS28 and delta J-HAQ in the both groups were similar and adjusted ORs of PD for DAS28 remission (0.85 [0.69-1.04]) and for J-HAQ remission (0.99 [0.67-1.45]) at 6 month were not statistically significant. There were significant differences in the percentage of patients who developed infections between the two groups (5.8% in PD group, 3.4% in non-PD group, p=0.002). Adjusted OR of PD for infections was 1.72 [1.10-2.69], which was significantly elevated. Conclusion: RA patients with PD had similar treatment response with those in the non-PD group, however, had higher disease activity, poorer physical function, and higher risk of infections compared to those without. These results may indicate that oral management is important for the better outcomes of patients with RA in the daily practice. References: [1] Nat Rev Rheumatol. 2017:606-20 [2] J Clin Rheumatl. 2012:180-4 [3] Med J Islam Repub. Iran. 2017:44 Acknowledgement: We thank all patients who participated in the IORRA survey and all of the members of the Institute of Rheumatology, Tokyo Women's Medical University, for the successful management of the IORRA cohort. Disclosure of Interests: Mayuko Hayashi: None declared, Ryoko Sakai Grant/research support from: Tokyo Women's Medical University (TWMU) has received unrestricted research grants for Division of Epidemiology and Pharmacoepidemiology of Rheumatic Diseases from Ayumi Pharmaceutical Co. Ltd., Bristol Meyers Squib, Chugai Pharmaceutical Co. Ltd., Nippon Kayaku Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Corp., and with which TWMU paid the salary of R.S. RS has received a research grant from Bristol-Meyers Squibb. Eiichi Tanaka Speakers bureau: Abbvie, Asahi Kasei pharma co., Bristol Myers Squibb, Chugai Pharmaceutical, Daiichi Sankyo Co., Eisai Pharmaceutical, Janssen Pharmaceutical K.K., Nippon Kayaku, Pfizer, Takeda Pharmaceutical, Taisho Toyama Pharmaceutical Co., and UCB Pharma., Takefumi Furuya Speakers bureau: the Asahi Kasei Pharma Corporation, Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Ono Pharmaceutical Co., Ltd., Pfizer Japan Inc., Takeda Pharmaceutical Co., Ltd., and UCB Japan Co. Ltd, Eisuke Inoue: None declared, Mai Abe: None declared, Mika Kawano: None declared, Eri Sugano: None declared, Naohiro Sugitani: None declared, Kumiko Saka: None declared, Moeko Ochiai: None declared, Yoko Shimizu: None declared, Rei Yamaguchi: None declared, Naoki Sugimoto: None declared, Katsunori Ikari: None declared, Atsuo Taniguchi: None declared, masayoshi harigai Grant/research support from: Tokyo Women's Medical University (TWMU) has received unrestricted research grants for Division of Epidemiology and Pharmacoepidemiology of Rheumatic Diseases from Ayumi Pharmaceutical Co. Ltd., Bristol Meyers Squib, Chugai Pharmaceutical Co. Ltd., Nippon Kayaku Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Corp., and with which TWMU paid the salary of MH. MH has also received research grants from AbbVie Japan GK, Eisai Co. Ltd., Takeda Pharmaceutical Co., Ltd., and Teijin Pharma Ltd., Hisashi Yamanaka Grant/research support from: AbbVie, Eisai, Bristol-Meyers, Novartis, Behringer, Astellas, Kaken, Nippon-Shinyaku, Pfizer, UCB, Ayumi, Ono, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, YLbio, Speakers bureau: Bristol-Meyers, Astellas, Pfizer, Daiichi-Sankyo, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, YLbio